Kontribusi dan Peran Gereja dalam Membangun Solidaritas Pelayanan Sosial di Asia - Angel Pengkhotbah Taromali Hulu; Dita Futri Anggraini; Malik Bambangan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The church is not only a building or building that is only used as a place of worship for Christians, but in the church it is also a place or forum for Christians to be able to grow together with each other, whether it is a spiritual or social form so that small communities are created even the largest. If the church is only understood as a building or building for worship, then it is likely to be considered not only as a terminology but also as a theological distort. So the church is a community of God, who has been called out of darkness into the light. The dynamics of church growth in Asia today are very diverse, and the problems of church growth are most affected by social problems, globalization, technological advancements, and cultural changes. In this context, it requires an important role of the church, namely from the way the church grows and the leadership of the church as an agent of change that is able to integrate Christian values with the demands of the times.